Supporting Teachers in Improving Formative Decision-Making: Design Principles for Formative Assessment Plans - van der Steen, Janneke; van Schilt-Mol, Tamara; van der Vleuten, Cees; Joosten-ten Brinke, Desirée (Frontiers in Education, 2022)
Formative assessment is considered as one of the most effective interventions to support teacher decision-making and improve education and student learning. However, formative assessment does not always meet these expectations. In order to be effective, formative assessment activities should be consciously and coherently planned aligned with other aspects of the curriculum and the decisions teachers wish to make based on these activities. While there is sufficient support for teachers to design formative assessment activities, no guidelines exist to help them tie these different activities together in an effective way. To support teachers in designing formative assessment plans informing formative decision-making, this study focused on the creation of a set of design principles. These design principles for formative assessment plans were formulated based on expert interviews and subsequently evaluated by future users. The result is a set of eight design principles that can be used and validated in educational practice.